Influence of sorghum grain supplementation on forage utilization by beef steers consuming immature bluestem - E.S. Vanzant; A.A. Beharka; R.C. Cochran; T.B. Avery; K.A. Jacques (Kansas Agricultural Experiment Station Research Reports, 1987)
Supplementing beef steers consuming immature bluestem with 0, 1, 2, or 4 lbs of sorghum grain daily did not affect forage intake. Thus, total intake increased as level of grain increased. Total dry matter, cell wall, and starch digestibilities were mildly depressed with increasing grain. Rumen fill and rates of passage were similar for all treatments, and differences in rumen fermentation characteristics were minimal.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Sorghum grain; Steers; Bluestem